Aspectos sociais e culturais sobre o futebol amador em Cuiabá : um estudo sobre o campeonato de futebol peladão - Oliveira, Sizernandes Freire de (2018)
Even with all the spectacularization that involves a high-performance professional sports activity, it is in everyday life, in the parks, in the public spaces, or even in improvised places, that the greater part of the population can, in fact, strengthen their contact with the activities amateur sports, especially amateur football. Sport emerges as a cultural manifestation for man, and has several meanings. According to Giulianotti (2010), football allowed different cultures and nations to construct particular forms of identity through their interpretation and practice of the game. Football is directly linked to society, capable of numerous social situations and manifestations that can be studied, not only sociological, but also anthropological and cultural. The main objective of the dissertation is to study the social, sporting and cultural aspects among the teams, fans, athletes and amateur soccer leaders in the municipality of Cuiabá-MT. The specific objectives of this research can be defined as follows: A) Identify the meanings of amateur football for the amateur soccer league agents named peladão; B) To investigate the financing strategies of amateur football in the peladão; C) Analyze the differences (similarities and ruptures) between the current amateur football and that practiced in the 1980s; D) To point out the maintenance difficulties (existence) of amateur soccer in Cuiabá-MT. The research problem is: what are the social, economic and cultural meanings of amateur football in the metropolitan region, present in the peladão championship? In this dissertation the research methodology used was qualitative. The proposal of this study is divided in three stages regarding the methodological procedures: the exploratory phase, the fieldwork with interviews and, finally, the analysis and treatment of the material collected in the field. The research intends to contribute in some way to the sociological studies of amateur soccer, strengthening the approach of the theme in the social sciences, as Toledo (2001) affirms, that carried out a balance of production in terms of research and publications and found that in 21 years 1980 to 2001), taking football as a social science theme, only two out of hundreds of publications have taken the "várzea soccer" or "the pebbles" as an object of study. The purpose of the dissertation is to contribute to the strengthening of the theme in the sociological studies on amateur soccer in the metropolitan region of Cuiabá-MT.